Circulating long noncoding RNA ZNFX1 antisense RNA negatively correlates with disease risk, severity, inflammatory markers, and predicts poor prognosis in sepsis patients. Issue 9 (March 2019) - Xu, Yahuan; Shao, Bibo
Abstract : Abstract: This study aimed to investigate the correlation of long noncoding RNA (lncRNA) ZNFX1 antisense RNA (ZFAS1) with disease risk, severity, inflammation markers, and prognosis in sepsis patients. A total of 202 sepsis patients were consecutively enrolled, and 200 healthy volunteers were also recruited as healthy controls (HCs). Plasma samples of all patients and HCs were collected. LncRNA ZFAS1 expression was determined by quantitative polymerase chain reaction assay and inflammatory cytokines levels were detected by enzyme-linked immunosorbent assay. The median value of lncRNA ZFAS1 expression in sepsis patients was (0.639 [0.325–1.071]), which was lower compared to HCs (1.957 [0.876–3.245], P < .001], and receiver operating characteristics (ROC) curve revealed that lncRNA ZFAS1 expression had a good diagnostic value for sepsis with area under curve (AUC) of 0.814 (95% confidence interval [CI]: 0.771–0.857). Spearman test disclosed that lncRNA ZFAS1 expression was negatively correlated with Acute Physiology and Chronic Health Evaluation (APACHE) II score ( r = −0.505, P < .001), and it was negatively associated with levels of C-creative protein ( r = −0.241, P = .001), tumor necrosis factor-α ( r = −0.253, P < .001), and interleukin (IL)-6 ( r = −0.177, P = .012) while positively associated with IL-10 level ( r = 0.173, P = .014). Also, lncRNA ZFAS1 expression was lower in survivor group compared to nonsurvivor group ( P < .001), and it presented with a good predictive value on distinguishing nonsurvivors from survivors in sepsis patients with AUC of 0.628 (95% CI: 0.538–0.717). Circulating lncRNA ZFAS1 expression negatively correlates with disease risk, severity, and inflammatory markers levels, and might predict worse survival in sepsis patients.